2015
DOI: 10.1515/sjdv-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Painless Multidermatomal Herpes Zoster in an Immunocompetent Elderly Male: a Case Report

Abstract: The varicella-zoster virus is the cause of both varicella and herpes zoster. The primary infection of varicella includes viremia and a widespread eruption, after which the virus persists in nerve ganglion cells, usually sensory. Herpes zoster is the result of reactivation of this residual latent virus. The first manifestation of zoster is usually pain, which may be severe and accompanied by fever, headache, malaise and tenderness localized to one or more nerve roots. The lymph nodes draining the affected area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Herpetic blisters are usually painful, but near-painless herpetic blisters have also been reported. 4,5 She was put on mechanical ventilatory support because of type 2 respiratory failure. Causes for fixed dilated pupils with altered sensorium were considered (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Herpetic blisters are usually painful, but near-painless herpetic blisters have also been reported. 4,5 She was put on mechanical ventilatory support because of type 2 respiratory failure. Causes for fixed dilated pupils with altered sensorium were considered (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of multidermatomal Herpes Zoster have been reported in the literature. Furthermore, only a handful number of cases with this manifestation were described in healthy immunocompetent individuals [ 9 , 10 ]. A recent case report by Beuerlein et al [ 11 ] summarised the published cases of multidermatomal HZ and found only 9 cases in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in our patient, the occurrence of HZ with complete absence of any preherpetic or postherpetic neuralgia is perplexing. At present, only a few cases of painless HZ have been described in the literature 10–13…”
Section: Discussionmentioning
confidence: 99%